Exploring Alternative Octane Specification Methods for Improved Gasoline Knock Resistance in Spark-Ignition Engines - Abdul-Manan, Amir F. N.; Kalghatgi, Gautam; Babiker, Hassan (Frontiers in Mechanical Engineering, 2018)
Different octane specification methods were evaluated under rising ethanol blending volumes by adopting a refinery economics model to represent a region in the U.S.. It was demonstrated that the traditional octane specification methods, such as the Anti-knock Index (AKI) used in the U.S., or the Research Octane Number (RON) and Motor Octane Number (MON) used in the EU, can lead to counterintuitive drop in octane sensitivity with increased availability of ethanol. This is undesirable for modern gasoline engines that require fuels with high RON and low MON, but it is a consequence of how a refinery reformulates the gasoline blendstock, resulting in more naphtha being used in the final composition. The use of a new specification method based on octane index (OI), with engine constant K = -1, internalizes the diminishing role that MON plays in modern engines, thus ensures that the desirable anti-knock quality is being met either through higher RON and/or higher sensitivity. Initial assessment suggests a potential engine efficiency benefit (~ 1.5%) to be gained simply by switching from an AKI-based specification method to an equivalent OI-based method.